The Influence of Maternal Age, Parity and Education on Infant Mortality in West Aceh Regency - Sukma Elida; Siti Maisyaroh Fitri Siregar; Arfah Husna; Dian Fera; Azwar Azwar (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2019)
One of the important index to reflect health status in a certain area is Infant Mortality Rate (IMR). IMR is also global soccioeconomic indicator in a population. Besides, The Statistical index indicates the quality of life, not only the quantity and number of death. It is the main health problem In Indonesia, There was 32 deaths per 1000 live births In Indonesia. The research was to analyze the influence of maternal age, parity, and education to infant mortality in West Aceh Regency. The research was quantitative with case control design, a case group was 45 mothers whose babies died when they were under one years old and a control group was 45 mothers whose babies were alive when they were under one year old. The maching was done on the babies based on their age and sex. The Data analyzed by using univariate and bivariate analysis with McNemar test, meanwhile, multivariate analysis with conditional logistic regression test at the significant level of 0.25. The Result of analysis in this research showed that maternal age and parity significanly influence of infant mortality. In the otherhand, maternal education did not significanly influence of infant mortality. The most significanly variable which influence of infant mortality was maternal age (OR=4.745). To Prevent Infant mortality from the variabel maternal age and parity, it is suggested for women to get merried at the age ≥20 years old, increases reproductive health education for female teenagers at schools and increases the conerage of using KONTAP (long term contracepcion) for women that have  more than four children. It is also suggest to provide adequate medical equipment to support the childbirth and increase the access of health facilities by optimizing village polycliclic and  It is also suggested to provide adequate medical equipment to support childbirth, increase the convenience of health facilities, and increase the access to health facilities by optimizing village polyclinics and midwives performance.